Early vascular remodeling role in arterial hypertension pathogenesis among young patients - I. V. Milyagina; V. A. Milyagin; M. V. Grekova; V. V. Kopteva (Кардиоваскулярная терапия и профилактика)
Aim. To investigate vascular wall stiffness in young patients, for examining early vascular remodeling role in arterial hypertension (AH) pathogenesis in young age. Material and methods. The study included 291 individuals: 169 normotensives and 122 AH patients aged 16-34 years. All participants underwent volume sphygmography (VaSera-1000, «Fukuda Denshi», Japan), blood pressure (BP) measurement in upper and lower extremity basins, elastic and muscular vessel elasticity assessment. Results. In young age, high elastic vessel stiffness was observed in 13.6% of normotensives, and in 50% of AH patients. For muscular vessels, this parameter was 11.2% and 35%, respectively. In systolo-diastolic AH, muscular vessel stiffness increased, in isolated systolic AH (ISAH) – elastic or elastic and muscular vessel stiffness is increased. About 50% of young ISAH individuals had increased BP on upper extremities only – «pseudo-hypertension». Conclusion. Early vascular remodeling plays an important role in AH pathogenesis among young people.